Unraveling the therapeutic landscape of approved non-peptide macrocycles - Zhonghua Li; Zhenqiang Zhang; Bin Yu (Acta Pharmaceutica Sinica B, 2025)
Non-peptide macrocyclic drugs possess unique structural advantages that allow them to target various biomolecules of interest and thus show therapeutic potential against various diseases such as cancer, infectious diseases, etc. This review article examines 34 non-peptide macrocyclic drugs approved between 2000 and 2024, with a particular focus on the optimization process of representative macrocyclic drugs such as natural macrocycles, natural product-inspired macrocycles, and de novo-designed macrocycles. We discuss their structural characteristics, highlighting how conformational rigidity and enhanced target specificity contribute to their efficacy. Design details of these new macrocyclic drugs are illustrated through successful examples, offering insights for optimizing macrocycles. Of note, macrocyclization of U-shaped lead structures represents a novel molecular skeleton editing strategy in de novo macrocycle drug design.